Protection of Private Equity Investors under the Dodd-Frank Act - Toyou, Doris (Journal of Law and Commerce, 2019)
In securities law, investor protection means that an issuer of securities, here partnership interests for private equity, must register with the Securities and Exchange Commission (“SEC”) and be subject to disclosure, reporting, record-keeping compliance and examination programs. This Article argues that the Dodd-Frank Act has fulfilled part of its objective to protect private equity investors by forcing private equity managers to disclose information on their operations. Disclosure has provided greater transparency about how the business of private equity is conducted. The increased SEC scrutiny started in 2014 has uncovered unfair practices and violations of fiduciary duties that sophisticated investors could not detect on their own. Notwithstanding this improved transparency, the Dodd-Frank Act still falls short of imposing the main tool securities laws uses to protect investors: that is, full and fair disclosure. In other words, Dodd-Frank does not provide all the required protections that are important for investors to assess the quality of their investments and make informed decisions. This Article offers to expand transparency by additional public disclosure of investment returns, fees, and managers’ income. For other policy issues unrelated to the protection of investors, that is, jobs or tax, Title IV of the Dodd-Frank Act does not offer the appropriate setting. Applying or enacting legislation concerning tax, labor or bankruptcy laws can better curve the controversial practices of private equity firms.